Understanding Impulse Buying Behavior: The Case of Blind Box Purchases in Indonesia - Melvina Lystiani Sandra Dewi, Made; D. Budoyo, Vernandhita; Mustikasari, Faranita (Jurnal Locus Penelitian dan Pengabdian, 2026)
Uncertainty-based merchandising, exemplified by the blind-box format, conceals product attributes to heighten consumer anticipation and transform purchase episodes into suspenseful experiences. This study investigates how perceived scarcity, perceived uncertainty, and fear of missing out (FOMO) jointly influence impulsive buying among Indonesian Generation Z consumers in the blind-box market. Data were collected via an online survey of 211 Gen Z respondents, and Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to evaluate both measurement and structural models. Results indicate that perceived scarcity (? = 0.21, p < .01) and perceived uncertainty (? = 0.24, p < .001) each significantly elevate FOMO (R² = .60), which in turn exerts a strong positive effect on impulsive buying (? = 0.45, p < .001; R² = .54). Moreover, both scarcity (? = 0.28, p < .001) and uncertainty (? = 0.32, p < .001) display direct effects on impulsive purchasing. Mediation analyses confirm that FOMO partially mediates these relationships. These findings extend uncertainty-promotion theory by demonstrating the synergistic role of outcome uncertainty and supply scarcity in amplifying loss-aversion processes and FOMO, thereby driving unplanned purchases. From a managerial perspective, calibrated scarcity mechanisms and managed uncertainty can be leveraged to stimulate consumer engagement while preserving trust. Future research should employ longitudinal designs and cross-cultural comparisons to further validate and generalize these insights.